A Passage in Time. (5th June 2013) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> In 1975 (Vol. 8.4, 201–218), S. P. Corder, during the course of his state-of-the-art review Error analysis, interlanguage and second language acquisition, focused on the recent literature on simplified linguistic systems and suggested that research had shown that interlanguage systems often resemble other simple codes such as pidgins or creoles '. . .now recognized to bear considerable resemblance to each other whatever their linguistic provenance' (p. 211). He then went on to suggest that the study of pidginisation and creolisation may help us better understand the L2 learning process.